Antibacterial and Anti-inflammatory Activities of Ppc-1, Active Principle of the Cellular Slime Mold Polysphondylium pseudo-candidum - Azelmat, Jabrane; Fiorito, Serena; Genovese, Salvatore; Epifano, Francesco; Grenier, Daniel (Medicinal Chemistry, 2015)
The diisopentenyloxy quinolobactin derivative 3-methylbut-2-enyl-4-methoxy-8-[(3- methylbut-2-enyl)oxy] quinoline-2-carboxylate, also named as Ppc-1, has been initially isolated from the fruiting bodies of the cellular slime mold Polysphondylium pseudo-candidum. Given that few data are available in the literature concerning the biological properties of this compound, this study was undertaken to evaluate its antibacterial and anti-inflammatory properties. Ppc-1 exerted antibacterial activity on the Gram negative periodontopathogen Porphyromonas gingivalis, while it had no such effect on the other bacterial species tested. The antibacterial activity of Ppc-1 appeared to result from its ability to permeate the cell membrane. Using the U937-3xΚB-LUC human monocytic cell line, Ppc-1 was found to dose-dependently inhibit the lipopolysaccharide-induced NF-ΚB activation, a signaling pathway that has been associated with inflammatory mediator secretion. In conclusion, Ppc-1, by exhibiting a dual mode of action including antibacterial and anti-inflammatory activities, may represent a promising targeted therapeutic agent for periodontal diseases.
Keywords: Quinolobactin